Efforts to Use Informants in Investigating Criminal Acts of Narcotics Abuse by the Narcotics Unit of the Bandar Lampung Police - Muhammad Fajri Akbar Perdana (Advances in Police Science Research Journal, 2021)
The existence of informants is very important in supporting the investigation of narcotics abuse cases. The problems in this thesis are the efforts of the Narcotics Unit to get informants, how they are used in investigations and the influencing factors. Researchers used the SWOT theory from Kearns, the motivation theory by Kreitner and Kinicki as well as the concepts of Narcotics, Psychotropics, and Other Addictive Materials, the Concept of Drug Abuse, the Concept of the Police Drug Unit, the Concept of Efforts, and the Concept of Investigation in accordance with the National Police Chief Regulation No. 6 of 2019 concerning Criminal Investigation. The research approach uses a qualitative approach using case studies. The research was carried out at the Bandar Lampung Police, the results of the research on the first problem illustrate that the investigator's efforts to obtain informants were carried out by utilizing informants who came from ex-convicts involved in drug cases and arrested perpetrators. Then the second problem illustrates that the use of informants is carried out when investigating narcotics abuse cases. Efforts to use informants can be seen when the investigation is carried out by means of interviews, interrogation, observation, and undercover buys. Furthermore, in the third problem, there are internal factors that support, namely the ability of investigators to use informants to provide information. Then the external factor is the reward in the form of money and feelings of revenge against other actors. Meanwhile, there are internal factors that hinder it, namely the limited budget to be given to informants and externally, the fear of the community being used as informants by the police. The conclusion is that investigators already have the ability to get informants, efforts to use informants in investigations are very helpful in conducting investigations. Suggestions from this thesis are the need to carry out an informant guidance system and the need to detect the selection of informants, and this thesis is used as a reference for other research.